Instagram in Arabic Learning: Mixed Methods to Investigate The Effectiveness and Errors of Speaking Skills - Zainul Arifin; Ayu Desrani; Suci Ramadhanti Febriani; Apri Wardana Ritonga; Ilya Husna (Arabic Education Program IAIN Pekalongan, 2022)
Social media grows very fast and it has an impact on the high intensity of users in social interaction. One of the media that is often exposed is Instagram, it encourages Arabic learning lecturers to internalize it in learning. Thus, this study aims to investigate the effectiveness of Instagram on the Arabic speaking skills of STAI Sabili Bandung students and analyze verbal language errors. The quantitative data in the form of pre-test and post-test results were analyzed through experimental methods. Meanwhile, the qualitative data were analyzed by using the inductive method to classify verbal language errors. The findings show that the speaking skills of STAI Sabili Bandung students have a positive significant increase in using Instagram as a means to develop Arabic speaking skills, but there are still errors in spoken language productivity such as vocabulary errors, sentence arrangement, and phrasing errors that are in accordance with the context of the sentence. The findings show that there is positive effect on Arabic speaking skills through the application of Instagram media evidenced by the significance value of Two-Sided p of <0.001 <0.05. The limitation of this study is the small sample size. So, it can hardly be generalized to a larger population. The researcher recommends further research to explore more detailed information with various research methods.